PENGARUH KESADARAN WAJIB PAJAK, PELAYANAN PERPAJAKAN DAN KEPATUHAN WAJIB PAJAK TERHADAP KINERJA PENERIMAAN PAJAK (Studi Kasus Pada Kantor Pelayanan Pajak Pratama Semarang Candisari) - Ardiani Ika Sulistyawati; Dian Indriana Tri Lestari; Novi Widi Tiandari (InFestasi, 2012)
To meet the expectations will increase the tax rules in development, the Directorate General of Taxes began to make efforts intensification of tax collection and extending the tax potential exploration. Consciousness, taxpayer compliance, which is partly that can affect the performance of tax revenues, supported by the existing service tax on the related tax services office. Improving the quality and quantity of services expected to increase the satisfaction to taxpayers as customers thus improving compliance in the field of taxation. The purpose of this study is to empirically examine, analyze the influence of taxpayer awareness, service tax, tax payer compliance to the performance of tax revenue. The samples in this study is the taxpayer the Tax Office Primary Semarang Candisari taken by accidental sampling method. The data used are primary data collected through the answers to every question in the list questionaire. Method of analysis using multiple linear regression. This research finds that either partially or simultaneously, awareness taxpayers, tax and compliance services taxpayers have a significant influence on the performance of tax revenue.